2019
DOI: 10.3390/polym11040572
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Structures and Structural Transitions of Copolyamides Derived from 1,4-Diaminobutane and Different Ratios of Glutaric and Azelaic Acids

Abstract: Copolyamides derived from even 1,4-butanediamine and different mixtures of odd dicarboxylic acids with a great difference in the number of methylene groups (i.e., glutaric and azelaic acids with 3 and 7 groups, respectively) have been synthesized, characterized and structurally studied. Calorimetric analyses revealed a complex behavior with multiple melting peaks associated to lamellar reordering and the presence of defective crystals. Equilibrium melting temperatures were evaluated and showed a eutectic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The biological production of diamines, such as 1,3-diaminopropane, 1,4-butanediamine, 1,5-pentanediamine, 1,6-diaminohexane, 1,8-diaminooctane, 1,10-diaminodecane, and 1,12-diaminododecane, as well as other aromatic diamines, was recently reviewed [ 163 ], paving the way for a wide family of sustainable polyurethanes and polyamides. This was the case, for instance, of the polymerization of 1,4-butanediamine with different mixtures of glutaric and azelaic acids [ 164 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…The biological production of diamines, such as 1,3-diaminopropane, 1,4-butanediamine, 1,5-pentanediamine, 1,6-diaminohexane, 1,8-diaminooctane, 1,10-diaminodecane, and 1,12-diaminododecane, as well as other aromatic diamines, was recently reviewed [ 163 ], paving the way for a wide family of sustainable polyurethanes and polyamides. This was the case, for instance, of the polymerization of 1,4-butanediamine with different mixtures of glutaric and azelaic acids [ 164 ].…”
Section: Broadening the Horizon: Bio-based Routes For Original Polymersmentioning
confidence: 99%
“…These polyamides presented a M w in the range 40,000-51,000 g/mol, a predominant melting peak in the range 220-244 • C, T d (thermal decomposition temperature) in the range 422-455 • C and a T g in the range 50-71 • C. The higher M w was achieved when AzA was 50% molar percentage in the acid mixture, while the lower T g was obtained for the homopolymer with 100% AzA. Results suggested that a similar predominant hydrogen bonding structure was present in all the analyzed polyamides [73].…”
Section: Polyamides Containing Azelaic Acidmentioning
confidence: 85%
“…Aromatic polyamides are classified as highperformance polymers for their high Tg, good resistance to chemicals, temperature, and Aliphatic polyamides, or nylons, are semicrystalline polymers with properties that change according to the ratio between amides and methylene groups. These materials are not biodegradable and possess great mechanical properties given by strong intermolecular hydrogen binding interactions [73]. Long-chain nylons, where the polar groups are separated by more than six carbon atoms, have both polyethylene properties and polyamide properties.…”
Section: Polyamides Containing Azelaic Acidmentioning
confidence: 99%
See 1 more Smart Citation